ANALISIS SPASIAL GUNA MENDUKUNG IDENTIFIKASI AWAL POTENSI NILAI KONSERVASI TINGGI (NKT) DI PT. BUMI PRATAMA KHATULISTIWA KECAMATAN SUNGAI AMBAWANG KALIMANTAN BARAT - Dewi, Puti Sari; Nugroho, Joko; Latifah, Siti (Universitas Tanjungpura, 2017)
Forest deforestation caused loss of habitat for endangered species. Changes in forest into oil palm plantation by PT Bumi Pratama Khatulistiwa (BPK) resulted in many conflicts with the community and make the loss of conservation value. Studies on areas that have a high conservation value necessary to maintain the stability of the clearing of forests to the environment is sustainable. Geographic information system technology (GIS) field of conservation is able to provide spatial information, determine the species habitat, analysis to find protected areas and mapping out areas of biodiversity.Â The purpose of this study to determine the ability of GIS technology in providing information for the early identification of areas with high conservation value and determine which area has high conservation value (HCV) in the concession area of PT BPK and surrounding villages. Research was conducted for two months.Â The research results show that GIS has enormous benefits in mapping out areas of high conservation value. Work on a large scale can be easily done and also save time, effort and cost. Location HCV 1 overlapping with the HCV 3 and 4 which are in the river, riparian and peat swamp forests. Location NKT 2 was not found, because most of the research area is an open area, there is no broad landscape. Location HCV 5 was not found, because most people in the study area does not depend anymore with natural forests.Â Oil palm plantations PT BPK give people easy access to the city, to buy daily necessities. Location HCV 6 is located within the concession area of PT BPK namely padagi sites. The site was used by the Dayak community to worship ancestors and offer prayers at tuah jubata (god almighty one).Keywords: Geographic Information System (GIS), High Conservation Value (HCV), PT BPK.